(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Informação@Profissões Vol. 1, n. 1/2 (2012) Link de acesso ao número http://www.uel.br/revistas/uel/index.php/infoprof/issue/view/874